SIGNIFICANCE OF AUTHENTIC MATERIALS IN TEACHING PROCESS WRITING (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Nowadays it is very important to know at least one foreign language. Technical university students study English as a Foreign Language (EFL) and we should not only rouse their learning interest but also give sound knowledge in the subject. This article emphasizes pros and cons of authentic materials in classrooms and provides some practical advice. There is no doubt that today English teachers have a lot of choices in terms of teaching materials. Choosing them we are to keep in mind that we should focus students’ attention not only on vocabulary and grammar structures but prepare them for real communication where the knowledge of culture is sometimes crucial. Thus the use of authentic materials can help solve this problem. There exist a lot of authentic materials like reading, newspapers, literature, video, TV, surveys, guest speakers, cultural quizzes / tests, role plays / dramatizations, songs, anecdotes, travel brochures, menus, catalogues, real estate pamphlets, phone books, CDs, the Internet, illustrations and so on. In this article we are going to deal with the most commonly used materials at EFL classes: reading (texts); video; computer programs.